UKRAINIAN ENLIGHTENERS POLAND (1956‒1970): DESTINY ON THE BACKGROUND OF THE DAY - Lashyn, Stefan (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2024)
Abstract The article of prof. Stefan Lashyn «Ukrainian Enlighteners in Poland (1956–1970)» is about the great migration of the Lemko-Ukrainians to the West Northern lands of Poland in the spring of 1947, the needy conditions of their residence and the lack of any cultural and educational conditions of life. Yet, nationally conscious Ukrainians achieved the creation of the Ukrainian Socio-Cultural Society (UCT) in 1956, which, in its turn, brought about the opening of Ukrainian classes in the lyceum in the town of Bartoschytsya. Ukrainian classes existed, taught and raised Ukrainian children during 1956–1970 and raised about two and a half hundred of Ukrainian patriots during these years. The article provides brief information about the Lyceum teachers, about those who put their soul, their knowledge into the hearts and the heads of young Ukrainians. Not all Lyceum graduates have carried out a Ukrainian word, the Ukrainian thought into the masses, but many of them have preserved that Ukrainian patriotic spirit that they had been put in by their favourite teachers in the lyceum. The purpose of the article is to show the desire of Ukrainians, deprived of all civil rights in communist Poland, for knowledge, for education, for preserving their national nature, their identity, almost heroic efforts of Lyceum teachers to preserve the Ukrainian spirit in students, to strengthen their knowledge of their native Ukrainian language, etc. Research methods. When writing the article, a variety of documents about Bartoshitsky Lyceum, memories of still living former teachers and especially graduates were used. The scientific novelty of the article is that still, except the author's monograph (see below), there were no such publications like that in Poland or Ukraine.